2005
DOI: 10.1117/1.1851513
|View full text |Cite
|
Sign up to set email alerts
|

Imaging ex vivo healthy and pathological human brain tissue with ultra-high-resolution optical coherence tomography

Abstract: The ability of ultra-high-resolution optical coherence tomography (UHR OCT) to discriminate between healthy and pathological human brain tissue is examined by imaging ex vivo tissue morphology of various brain biopsies. Micrometer-scale OCT resolution (0.9x2 microm, axialxlateral) is achieved in biological tissue by interfacing a state-of-the-art Ti:Al2O3 laser (lambda(c)=800 nm, delta lambda=260 nm, and P(out)=120 mW exfiber) to a free-space OCT system utilizing dynamic focusing. UHR OCT images are acquired f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(58 citation statements)
references
References 41 publications
0
57
0
1
Order By: Relevance
“…10,11 Conceptually, it has been compared to ultrasound scanning. 12 Both ultrasound and OCT provide real-time structural imaging, but unlike ultrasound, OCT is based on low-coherence interferometry, using broadband light to provide cross-sectional, high-resolution subsurface tissue images.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…10,11 Conceptually, it has been compared to ultrasound scanning. 12 Both ultrasound and OCT provide real-time structural imaging, but unlike ultrasound, OCT is based on low-coherence interferometry, using broadband light to provide cross-sectional, high-resolution subsurface tissue images.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Clinical applications of OCT have been mainly in ophthalmology, however, over the last 20 years it has been extended to cancer detection in a variety of tissues. 53,54 One of the first studies on ex vivo brain tissue by Bizheva et al 55 was reported in which the OCT signal was used to distinguish between healthy brain and multiple types of brain tumors. This study claims the source of OCT signal contrast comes from differences in cell nuclei, cysts, microvasculature, and microcalcifications in brain tissue.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Previous attempts at creating large 3-D data sets from tissue have used methods producing poor contrast, poor depth penetration, or that successively remove tissue as the 3-D volume is imaged. [3][4][5][6] Thus, past 3-D reconstruction techniques fail to improve upon the most important limitations of traditional histology. But 3-D reconstructions of clarified tissue using MPM showed excellent cellular contrast; sufficient depth, such that entire biopsy specimens could be imaged; and compatibility with subsequent traditional processing, including preservation of immunostain capability with the few antibodies tested.…”
Section: Commentmentioning
confidence: 99%
“…More recent ones include high-resolution x-ray computed tomography 1,2 and optical coherence tomography. 3,4 They have the advantages of being applicable to unprocessed fresh tissue and allowing complete 3-dimensional visual examination while leaving tissue unaltered and amenable to further characterization. While efforts in these fields continue, neither technique is able to produce images of sufficient resolution and contrast for adequate routine pathology evaluation.…”
mentioning
confidence: 99%